Melatonin Promotes the In Vitro Development of Microinjected Pronuclear Mouse Embryos via Its Anti-Oxidative and Anti-Apoptotic Effects - Tian, Xiuzhi (Int J Mol Sci, 2017)
CRISPR/Cas9 (Clustered regularly interspaced short palindromic repeats) combined with pronuclear microinjection has become the most effective method for producing transgenic animals. However, the relatively low embryo developmental rate limits its application. In the current study, it was observed that 10(−7) M melatonin is considered an optimum concentration and significantly promoted the in vitro development of murine microinjected pronuclear embryos, as indicated by the increased blastocyst rate, hatching blastocyst rate and blastocyst cell number. When these blastocysts were implanted into recipient mice, the pregnancy rate and birth rate were significantly higher than those of the microinjected control, respectively. Mechanistic studies revealed that melatonin treatment reduced reactive oxygen species (ROS) production and cellular apoptosis during in vitro embryo development and improved the quality of the blastocysts. The implantation of quality-improved blastocysts led to elevated pregnancy and birth rates. In conclusion, the results revealed that the anti-oxidative and anti-apoptotic activities of melatonin improved the quality of microinjected pronuclear embryos and subsequently increased both the efficiency of embryo implantation and the birth rate of the pups. Therefore, the melatonin supplementation may provide a novel alternative method for generating large numbers of transgenic mice and this method can probably be used in human-assisted reproduction and genome editing.